Potential Animal and Environmental Sources of Q Fever Infection for Humans in Queensland. (10th May 2013) - Tozer, S. J.; Lambert, S. B.; Strong, C. L.; Field, H. E.; Sloots, T. P.; Nissen, M. D.
Summary Q fever is a vaccine‐preventable disease; despite this, high annual notification numbers are still recorded in Australia. We have previously shown seroprevalence in Queensland metropolitan regions is approaching that of rural areas. This study investigated the presence of nucleic acid from Coxiella burnetii, the agent responsible for Q fever, in a number of animal and environmental samples collected throughout Queensland, to identify potential sources of human infection. Samples were collected from 129 geographical locations and included urine, faeces and whole blood from 22 different animal species; 45 ticks were removed from two species, canines and possums; 151 soil samples; 72 atmospheric dust samples collected from two locations and 50 dust swabs collected from domestic vacuum cleaners. PCR testing was performed targeting the IS1111 and COM1 genes for the specific detection of C. burnetii DNA. There were 85 detections from 1318 animal samples, giving a detection rate for each sample type ranging from 2.1 to 6.8%. Equine samples produced a detection rate of 11.9%, whilst feline and canine samples showed detection rates of 7.8% and 5.2%, respectively. Native animals had varying detection rates: pooled urines from flying foxes had 7.8%, whilst koalas had 5.1%, and 6.7% of ticks screened were positive. The soil and dust samples showed the presence of C. burnetii DNA ranging from 2.0 to 6.9%, respectively. These data show that specimens from a variety of animal species and the general environment provide a number of potential sources for C. burnetii infections of humans living in Queensland. These previously unrecognized sources may account for the high seroprevalence rates seen in putative low‐risk communities, including Q fever patients with no direct animal contact and those subjects living in a low‐risk urban environment.